2015
DOI: 10.2139/ssrn.2683287
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Routine Interdependence and Skillful Accomplishment on the Coordination of Standardizing and Customizing

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link 1 THE INFLUENCE OF ROUTINE INTERDEPENDENCE AND SKILLFUL ACCOMPLISHMENT ON THE COORDINATION OF STANDARDIZING AND CUSTOMIZING ABSTRACTThis paper advances understanding of the coordination of interdependence between multiple intersecting routines and its influence on the balancing of coexisting ostensive patterns. Building on a professional service routine -the deal app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 69 publications
2
54
0
2
Order By: Relevance
“…The authors show that the same actant engaged differently has a more or less generative effect. Spee et al (2016) make a similar observation about the flexibility of routine enactment. They examine intersections between routines in the context of property catastrophe reinsurance, a financial service where it is crucial to create contracts that balance standardized and customized features.…”
Section: How Do Routines Interact?mentioning
confidence: 64%
See 1 more Smart Citation
“…The authors show that the same actant engaged differently has a more or less generative effect. Spee et al (2016) make a similar observation about the flexibility of routine enactment. They examine intersections between routines in the context of property catastrophe reinsurance, a financial service where it is crucial to create contracts that balance standardized and customized features.…”
Section: How Do Routines Interact?mentioning
confidence: 64%
“…When intensive care unit (ICU) physicians engage in the handoff routine, for instance, providing information "out of order" can signal that it is time to have a more extended conversation in order to convey salient or problematic issues (LeBaron et al 2016). Similarly, Spee et al (2016) show that the same subroutine may have different meanings and call out different actions when it is enacted in a different part of the overall routine. Sequence is just one feature of the connections that create meaning.…”
Section: Action In Routines Is Situatedmentioning
confidence: 99%
“…Only after working examples of the new routines had been developed in operational trials, could actors in the strategic units select and prepare a standardized representation of the new routine (the contract and written procedures) for large-scale replication. While prior studies have shown how artifacts enable stability and change (Turner and Rindova, 2012;D'Adderio, 2014) and support ecologies of routines (Seele and Grand, 2016;Spee et al, 2016), future research could explore how artifacts provide anchors or fixed points around which new patterns of action and routines emerge and stabilize over time (Birnholtz et al, 2007) and adapt to the local needs (Jonsson and Foss, 2011).…”
Section: Future Researchmentioning
confidence: 99%
“…D'Adderio (2014) shows how artifacts are used during the transfer phase of replication to provide consistency and modified in the posttransfer phase to facilitate variation and adaptation. Finally, Seele and Grand (2016) and Spee et al (2016) show how artifacts perform a key role in supporting the interconnection among different routines.…”
Section: Insights From Practice Researchmentioning
confidence: 99%
“…Although scholars address the origins and evolution of organizational routines and capabilities at the macro level (Zollo and Winter, 2002;Romme et al, 2010), we still need to develop our knowledge about how and why they emerge at the micro level (Salvato and Rerup, 2011;Witt, 2011;Bapuji et al, 2012;Felin et al, 2012). Yet this is not a trivial question: routines involve multiple actors who may be unevenly willing to participate or not share the same vision of the routine (Feldman and Rafaeli, 2002;Howard-Grenville, 2005;Turner and Rindova, 2012;Spee et al, 2016). Two groups thus might not achieve the same degree of routinization or the same pace of routines' emergence, due to such differences between their participants.…”
Section: Introductionmentioning
confidence: 99%